Advanced Glycation End Products in Disease Development and Potential Interventions - Yihan Zhang; Zhen Zhang; Chuyue Tu; Xu Chen; Ruikun He (Antioxidants)
Advanced glycation end products (AGEs) are a group of compounds formed through non-enzymatic reactions between reducing sugars and proteins, lipids, or nucleic acids. AGEs can be generated in the body or introduced through dietary sources and smoking. Recent clinical and animal studies have highlighted the significant role of AGEs in various health conditions. These compounds accumulate in nearly all mammalian tissues and are associated with a range of diseases, including diabetes and its complications, cardiovascular disease, and neurodegeneration. This review summarizes the major diseases linked to AGE accumulation, presenting both clinical and experimental evidence. The pathologies induced by AGEs share common mechanisms across different organs, primarily involving oxidative stress, chronic inflammation, and direct protein cross-linking. Interventions targeting AGE-related diseases focus on inhibiting AGE formation using synthetic or natural antioxidants, as well as reducing dietary AGE intake through lifestyle modifications. AGEs are recognized as significant risk factors that impact health and accelerate aging, particularly in individuals with hyperglycemia. Monitoring AGE level and implementing nutritional interventions can help maintain overall health and reduce the risk of AGE-related complications.